National origin as a means of customer segmentation – an analysis of mobile communications users in a GCC country. Issue 4 (12th June 2017) - Gerpott, Torsten J.; May, Sebastian; Nas, Gokhan
Abstract : Purpose: In the field of mobile communications services (MCS), it is of importance to segment MCS users to support operators in better tailoring their offers to the needs of specific customer groups. This paper analyzes the suitability of national origin of MCS subscribers to segment residential customers into groups with significantly diverging usage behaviors in a sample living in one of the Gulf Cooperation Council (GCC) member states with a large share of expatriates in its population, particularly from South Asian countries. If MCS use patterns vary considerably between nationals, South Asian migrants and other foreign nationalities, it makes much sense to segment customers at least into these three groups. Design/methodology/approach: The investigation applies discriminant and regression analysis on a sample of 4, 892 residential postpaid MCS customers in a GCC country. The sample comprises individual usage data of 2, 446 national citizens and an equal number of non-nationals between July 2014 and July 2015, living in the focal country. The data set was extracted from the billing and customer management systems of a collaborating mobile network operator (MNO). Findings: The results imply that national origin is a highly significant predictor of individual MCS usage. Nationals and all expatriates primarily differ in international voice and SMS usage but not in established national MCS and mobile internet use intensity. Among expatriates, South Asians consume more national and international voice minutes than migrants originating from other foreign nations. Research limitations: The analysis is based on objective MCS usage data retrieved from an MNO's data warehouse. It lacks information on customer perceptions of the utility of various MNO service categories and on other individual characteristics, such as the customers' level of education or language proficiency. To overcome this limitation, empirical research is needed that incorporates additional objective customer descriptors as well as subjective perceptual constructs. Practical implications: MNOs are well advised to develop service bundles and tariff portfolios specifically designed for nationals and for different groups of expatriates. Originality/value: The paper extends the literature on MCS usage behavior in Arab states in general and on customer MCS usage segmentation based on individuals' national citizenship in particular.